ANALISIS RASIO KEUANGAN PADA PT SRI REJEKI ISMAN TBK TAHUN 2015 – 2017 - Chika Yunita Putri; Sri Hartono; Ida Aryati (ITB AAS INDONESIA Surakarta, 2019)
Analyzing financial statements can help stakeholders choose and evaluate information about the condition of the company. Financial ratio analysis can be compared using financial statements for at least the last 2 (two) years. The purpose of this study is to determine the level of liquidity ratio, solvency, profitability and activity at PT Sri Rejeki Isman Tbk in 2015 – 2017. This study uses a quantitative descriptive method and uses techniques of liquidity ratio analysis, solvability, profitability and activity. The results of this study are the liquidity ratios of 2015 – 2017 each always increasing and the company is in good condition. Solvability ratios during 2015 – 2017 always increase and the company is in good condition, even though in DER 2015 and 2016 the company is in a bad condition. The profitability ratio of 2015 – 2017 always increases and the company is said to be in good condition. While the activity ratios of 2015 – 2017 always increase but the company is said to be less good, but the inventory turnover in 2015 and 2016 and the total assets turnover in 2015 is said to be good Overall data analysis of the four ratios shows the growth of company value every year, namely 2015 – 2017 always increases and the company tends to be in good condition. This means that indirectly PT Sri Rejeki Isman Tbk (Sritex) has no financial problems. Keyword : liquidity ratio, solvency ratio, profitability ratio, activity ratio